2018
DOI: 10.3846/jbem.2018.1539
|View full text |Cite
|
Sign up to set email alerts
|

The Timing of Initial Public Offerings – Non-Numerical Model Based on Qualitative Trends

Abstract: The objective of this study is to develop a qualitative model supporting chief financial officers (CFOs) while considering the timing of initial public offerings (IPOs) under conditions of underdeveloped capital markets, where decision making is often made under information shortage. A lack of adequate statistical data in connection with turbulently changing environment suggests that additional research is needed to develop new IPO timing models based not only on statistical analyses. We used a qualitative res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…Second, these listing markets have experienced different economic developments and growths. Economic growth plays an important role on IPO activity and investor perceptions (La Porta et al, 1997;Gupta et al, 2018;Meluzín et al, 2018;Rija, 2019). Thus, the moderating effect of economic growth on the relationship between culture and IPO underpricing are demonstrated, thereby supplementing to the existing IPO underpricing literature.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…Second, these listing markets have experienced different economic developments and growths. Economic growth plays an important role on IPO activity and investor perceptions (La Porta et al, 1997;Gupta et al, 2018;Meluzín et al, 2018;Rija, 2019). Thus, the moderating effect of economic growth on the relationship between culture and IPO underpricing are demonstrated, thereby supplementing to the existing IPO underpricing literature.…”
Section: Introductionmentioning
confidence: 93%
“…It is demonstrated that investor sentiment, especially during a bull market, has a systematic impact of stock returns (Cornelli et al, 2006;Zhang et al, 2019). Therefore, economic growth also plays an important role in the stock markets, and has an effect on IPO activity (La Porta et al, 1997;Gupta et al, 2018;Meluzín et al, 2018). The prosperity economy contributes to "hot issue" markets (Ritter, 1984), which are characterized by less frequent price deviations (Lim & Brooks, 2010), high IPO volumes (La Porta et al, 1997;Gupta et al, 2018), and high levels of initial return (Ritter, 1984;Rija, 2019).…”
Section: The Moderating Effect Of Economic Growthmentioning
confidence: 99%
See 1 more Smart Citation
“…The evidence available in the sphere of research shows that market does not follow the perfect world scenario, and the prices do not just follow the random walk pattern being an asymmetric fat-tailed distribution; decreasing the possibility for the future prediction of the stocks (Lo & MacKinlay, 1988;Vyklyuk et al, 2013). The implied market expectation is the key to investor's decisions, at the point where personal expectations diverge from the market ones, and it is the key to adjusting the contents of portfolio to take advantage of what is known as market error (Barr & Campbell, 1997;Meluzín et al, 2017;2018a;2018b;Szumilo et al, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Decision about implementation of new system (APS) or improving the current MRP II planning process involve risks, which should be considered, same as for exemple in the entering on capital markets (Meluzín et al, 2012). Output from both of the systems is not comparable.…”
Section: Introductionmentioning
confidence: 99%